1986
DOI: 10.1002/bbpc.19860901216
|View full text |Cite
|
Sign up to set email alerts
|

Separation Mechanism of a Photoinduced Electron‐Hole Pair in Metal‐Loaded Semiconductor Powders

Abstract: Metals J Photochemistry 1 Photoelectrochemistry J Semiconductors J SurfacesPhotocatalytic activities of metal loaded CdS and p-GaP semiconductor powders were measured for ammonia production from aqueous N, solution and hydrogen evolution from ethanol-water mixture. The higher activity was obtained for the CdS loaded with the metal having a higher work function. On the other hand, the metal-loading on p-GaP powders showed a slight increase in the activity with loading lower work function metals. The numerical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…Noble metals deposited on the semiconductor particles have been shown to improve photocatalytic electron transfer processes at the semiconductor interface [18,25,[54][55][56]. As the hole transfer at the semiconductor/electrolyte is improved by the presence of a metal deposit we expect greater amounts of electron accumulation within the semiconductor nanocrystallites.…”
Section: Improved Photocurrent Responsementioning
confidence: 98%
See 1 more Smart Citation
“…Noble metals deposited on the semiconductor particles have been shown to improve photocatalytic electron transfer processes at the semiconductor interface [18,25,[54][55][56]. As the hole transfer at the semiconductor/electrolyte is improved by the presence of a metal deposit we expect greater amounts of electron accumulation within the semiconductor nanocrystallites.…”
Section: Improved Photocurrent Responsementioning
confidence: 98%
“…It has been shown that the photocatalytic electron transfer processes at the semiconductor interface can be greatly enhanced by depositing a noble metal on the semiconductor particle [18,25,[54][55][56]. The photogenerated holes are capable of oxidizing thiocyanate ions at the semiconductor interface [57].…”
Section: Photocatalytic Oxidationmentioning
confidence: 99%
“…Mass transfer of reactants Figure 3 summarizes the parameters that are highlighted according to the six processes. This review gives a broad and rather conceptual description only, rather than detailed discussion on the specific materials, which can be found in different reviews [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The author trusts that the understanding of these physicochemical properties leads to "photocatalyst materials by design" where the electronic structure of the semiconductor, interface development, and electrocatalytic properties are fully connected to achieve the complex sequential processes to achieve finally overall water splitting.…”
mentioning
confidence: 98%
“…In semiconductors, one of the driving forces of charge transfer is band bending. Figure 3 depicts the band bending that occurs when an n-type semiconductor is in contact with a solution [7]. In this case, the majority charges (electrons) near the interface of the semiconductor transfer into the solution until the potentials are equilibrated; i.e., the Fermi level (E F / equals the redox potential (E redox ) in the solution while preserving the band edge positions (pinning).…”
Section: Photon Absorption and Its Correlation With Photocatalyst Parmentioning
confidence: 99%
“…The H 2 O splitting is rather special case where chemical potential of electrons in the electrolyte may vary in between the H C /H 2 and the O 2 /H 2 O redox potentials. The figure gives a concept of Schottky barrier formation [7,8], extent of which is influenced by the Fermi level of semiconductor and the work function of the metals. In comparison with the bare semiconductor surface that is positively charged, metal particles are relatively negatively charged, enhancing the charge separation.…”
Section: Photon Absorption and Its Correlation With Photocatalyst Parmentioning
confidence: 99%